The efficacy of esmolol, remifentanil and nitroglycerin in controlled hypotension for functional endoscopic sinus surgery - Alkan,Aslı (2021)
Abstract Introduction Controlled hypotension is a reversible procedure in which the patient’s baseline mean arterial blood pressure is reduced by 30% and sustained at 60-70 mmHg during the procedure. It decreases blood loss and provides clear surgical field during the procedures. Objectives The purpose of this study was to compare the efficacy of controlled hypotension agents esmolol, remifentanil, and nitroglycerin in functional endoscopic sinus surgery, in terms of hemodynamic changes and impact on the surgical efficiency. Methods The research was carried out as a cohort study. Patients who underwent functional endoscopic sinus surgery were randomized into 3 groups. Controlled hypotension was achieved with remifentanil (Group R), esmolol (Group E) and nitroglycerin (Group N). The efficacy of the drugs was tested by comparing the length of time with the targeted mean arterial pressure, the amount of anesthetics used, surgical field bleeding score and surgeon’s satisfaction. Results Between May to December 2015, 60 patients were included and randomized equally into 3 different study groups. The median of the length of time with the targeted mean arterial pressure was shorter in the Group R when compared with Group E (p = 0.01) and Group N (p = 0.14). The amount of volatile anesthetics used was 25.0 mL (15-51), 43.0 mL (21-105) and 40.0 mL (26-97) in Groups R, E and N, respectively (p < 0.001). While there was more bleeding with nitroglycerin, surgical field bleeding scores were lower in Group R when compared with esmolol (p = 0.001) and nitroglycerin (p < 0.001). The analysis of surgeon’s satisfaction scores concluded that surgeons were more satisfied with the group R (100%), when compared with group E (60%) and group N (30%) (p < 0.001). Conclusion Less volatile agent, short time to achieve controlled hypotension, stable blood pressure, lower surgical field bleeding scores and larger length of time with the targeted mean arterial pressure were found as the advantages of Remifentanil. Less costly, efficiency of achieving the targeted median arterial pressure and less postoperative complications were the advantages of nitroglycerin. In functional endoscopic sinus surgery procedures, appropriate controlled hypotensive agents should be selected according to the patients’ characteristics and advantages/disadvantages of the drugs.